Composition and Antibacterial Activity of Essential Oils from Aerial Parts of Salvia lerrifolia Populations from Iran. Issue 2 (3rd March 2020) - Sarhadi, Elham; Nejad-Ebrahimi, Samad; Hadjiakhoondi, Abbas; Manayi, Azadeh
Abstract: Salvia leriifolia Benth is a perennial herbaceous plant and belongs to the Lamiaceae family; distributes among dry and warm regions in Iran. In the present study, the chemical compositions and antibacterial activity of essential oils from aerial parts of S. leriifolia collected from six natural habitats in North-East of Iran have been investigated. The essential oils were obtained by the hydrodistillation method by using a Clevenger type apparatus. The chemical composition of oils has been analyzed with GC/FID and GC/MS methods. The highest yield of oil was recorded from Kalateh-ye Hizomi (0.74 %) and the lowest amount obtained for Torbat-e Heydarieh sample (0.17 %). The major compounds characterized in oils were shyobunol (1.8-22.4 %), 1, 8-cineole (6.2-14.1 %), β-pinene (5.3-13.1 %) and α-pinene (1.0-5.1 %). The highest antibacterial activity against Staphylococcus aureus detected from Kalateh-ye Hizomi (MIC=0.47 mg/mL) and lowest activity reported from Marus (MIC=1.87 mg/mL).